2013
DOI: 10.4103/2045-080x.123228
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication and the advisory role of pharmacists in Riyadh, Saudi Arabia

Abstract: Background: Self-medication with over-the-counter (OTC) remedies is a common practice in both developed and developing countries; however, inappropriate self-medication can have adverse effects and may contribute to the emergence of drug-resistant pathogens. A consultation with pharmacists plays a crucial role in providing efficient professional guidance advice for appropriate use of OTC medicines. Aims: This paper investigated the situations in which patients ask a pharmacist for advice and the factors that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 11 publications
3
19
0
Order By: Relevance
“…The findings support the prevalence of self medication in previous studies [10,11] done at Saudi Arabia. It is worth noting that prevalence rate in another study [15] at Bahrain University students is 86% and almost similar results were found in one study [17] at Kuwait i.e.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings support the prevalence of self medication in previous studies [10,11] done at Saudi Arabia. It is worth noting that prevalence rate in another study [15] at Bahrain University students is 86% and almost similar results were found in one study [17] at Kuwait i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Herbal stores (QU= 4.2%, BPC=4.9%) and street markets (QU=1.4%, BPC=1.6%) are least used source for obtaining self medication. The availability of wide range of medications makes pharmacy as most important choice of getting medications [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Arab countries including Saudi Arabia, the prevalence of SM ranges from 35% to 92% [10][11][12][13][14]. Literature shows that most of the studies related to self-medication have been conducted among healthcare professionals or students, and there are only few studies concerned with general public of Saudi Arabia [11,[15][16][17]. Self-medication has not got the attention it deserves as a research topic.…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, OCPs are available over-the-counter without prescription, and a pharmacist’s advice might sometimes be a user’s only source of information. 10 , 11 Self-medication may result in inappropriate use of pills and consequently poor efficacy. However, women tend to start contraception on their own because of high fertility rates, less accessibility to health care for women, and large families.…”
Section: Introductionmentioning
confidence: 99%